Experimental Research on Fracture Characteristics of Reactive Powder Concrete in Different Volume Content of Steel Fiber - Wenzhen Wang; Haixiao Lin; Xiaogang Wu; Yuyao Zhao; Ziyu Hu; Pengshuai Wang; Menglong Zhou (Geofluids)
The fracture characteristics of reactive powder concrete in different volume content of steel fiber are researched in this paper, combining with the photoelastic coating method and the mathematical analytical software MATLAB. More precisely, the wholly integrated initiation, stable propagation, and final failure stages of precast cracks in three-point bending specimens of reactive powder concrete in different volume content of steel fiber are directly recorded and systematically analyzed. Besides, the photoelastic fringe distribution graphs from the vicinity of the precast cracks of specimens are obtained. Based on the experimental results and fracture mechanics theory, the mechanical property of reactive powder concrete, fracture energy, ductility index, initial fracture toughness, and unstable fracture toughness are quantitatively and qualitatively analyzed. The research achievements indicate that there is a stable crack propagation process before the instability failure of the three-point bending beam specimen of reactive powder concrete. The fracture process of the structure includes three stages, namely, the crack initiation, stable propagation, and instability failure. The order of the photoelastic fringe, critical effective crack length, crack initiation load, and maximum load of test parameters in the three-point bending beam specimen of reactive powder concrete increases with the increase of the fiber volume ratio. Based on the numerical treatment for the whole curves of each specimen group, the softening curve and the double fracture parameters of reactive powder concrete are obtained. Besides, the calculated critical effective joint length, initiation toughness, toughness increment, and unstable fracture toughness increase with the increase of the steel fiber volume ratio, by analyzing the measured initiation load, maximum load, and critical effective joint length. The research results can be treated as an important basis and reference for the engineering design and safety assessment of reactive powder concrete.